2015
DOI: 10.1093/petrology/egv057
|View full text |Cite
|
Sign up to set email alerts
|

A MASH Zone Revealed: the Mafic Complex of the Sierra Valle Fértil

Abstract: The Sierra Valle Fe ´rtil Complex of west-central Argentina represents a section of the Ordovician ($470 Ma) Famatinian arc and exposes a continuous, tilted crustal arc section ranging in depth from $12 to 32 km ($4-8 kbar pressure). This arc section exposes the complete compositional architecture from ultramafic and mafic rocks to upper crustal granodiorites. Field and compositional data are presented to document the deep ($6-8 kbar) mafic complex of the Sierra Valle Fe ´rtil. The mafic complex is composed of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
71
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 108 publications
(73 citation statements)
references
References 110 publications
2
71
0
Order By: Relevance
“…Karakas and Dufek, 2015) and thus call for fractionation as the primary means for producing silicic magmas (e.g. Jagoutz, 2010;Lee and Bachmann, 2014;Rioux et al, 2010;Walker et al, 2015). Whereas we do not contest that the latter may be the case in several geologic settings, we stress that the efficiency of assimilation is strictly dependent on the thermal evolution and the compositional and tectonic conditions of the intruded crust.…”
Section: Discussionmentioning
confidence: 73%
“…Karakas and Dufek, 2015) and thus call for fractionation as the primary means for producing silicic magmas (e.g. Jagoutz, 2010;Lee and Bachmann, 2014;Rioux et al, 2010;Walker et al, 2015). Whereas we do not contest that the latter may be the case in several geologic settings, we stress that the efficiency of assimilation is strictly dependent on the thermal evolution and the compositional and tectonic conditions of the intruded crust.…”
Section: Discussionmentioning
confidence: 73%
“…The greater diversity of applied pressure‐estimation techniques for granitoids and paragneisses from the Garm massif (Al‐in‐Hbl, GASP, and pseudosection modeling) compared to granitoids from the Gissar batholith (only Al‐in‐Hbl) reflects the greater lithologic diversity of the Garm massif. We speculate that exposures of rare, deformed mafic and ultramafic rocks reported in the Garm massif [ Budanov , ; Brookfield , ] may represent the upper MASH zone of the Gissar arc [e.g., Walker et al , ].…”
Section: Discussionmentioning
confidence: 99%
“…6A). Although, there is not much data (to our knowledge) on the actual thickness of the MASH zone, available studies suggest that it is most likely comprised between 1 and 10 km thick (e.g., Jackson et al, 2002;Walker et al, 2015). Jackson et al (2002) showed that 2 km was enough to strongly influence the compositional evolution of the magmatic products segregated from the MASH zone.…”
Section: Model Setup Of An Applicationmentioning
confidence: 99%
“…In migmatitic orthogneiss from the Gföhl Unit (Bohemian Massif), Hasalová et al (2008a) described 100-m scale pervasive flow from an external source produced migmatitic textures of high melt fraction. In the Ordovician Sierra Valle Fertil Complex of west-central Argentina, Walker et al (2015) studied an exposed lower crustal arc section. Based on petrological and geochemical studies, the authors show that the mafic section (mainly gabbronorites) was the locus of prolonged periods of (cyclic) magma injection, crystallization, and assimilation, with very efficient melt segregation at the kilometer scale.…”
Section: Introductionmentioning
confidence: 99%